On existence, multiplicity, uniqueness and stability of positive solutions of a Leslie–Gower type diffusive predator–prey system - Zhou, Jun (Nonlinear Analysis: Modelling and Control, 2014)
In this paper, we consider a Leslie–Gower type diffusive predator–prey system. By using topological degree theory, bifurcation theory, energy estimates and asymptotic behavior analysis, we prove the existence, multiplicity, uniqueness and stability of positive steady states solutions under certain conditions on parameters.
Keywords: Leslie–Gower type diffusive predator–prey system; positive steady state solutions; uniqueness; multiplicity; stability